Paediatric abdominal pain in the time of COVID-19: a new diagnostic dilemma. Issue 9 (21st September 2020) - Harwood, Rachel; Partridge, Roland; Minford, Joanne; Almond, Sarah
Abstract: The diagnostic uncertainty for children with abdominal pain has increased during the COVID-19 pandemic with the additional consideration of both COVID-19 and paediatric inflammatory multisystem syndrome—temporally associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (PIMS-TS) alongside appendicitis, mesenteric adenitis and other less common causes of abdominal pain. We describe the cases of two children who presented with severe abdominal pain, non-bilious vomiting and high temperatures during the UK's first peak of the COVID-19 pandemic. Laboratory and abdominal ultrasound features were similar for both children but symptom progression in combination with cross-sectional abdominal imaging enabled differentiation between PIMS-TS and appendicitis with concurrent COVID-19. These cases highlight the importance of regular clinical review, multidisciplinary working and the utility of early cross-sectional imaging to determine the underlying condition.